2020
DOI: 10.1007/s00425-020-03354-w
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary insights into FYVE and PHOX effector proteins from the moss Physcomitrella patens

Abstract: Phosphatidylinositol 3-phosphate (PtdIns3P) is one of the five different phosphoinositides (PPIs) species in plant cells, which regulate several aspects of plant growth and development, as well as responses to biotic and abiotic stresses. The mechanistic insights underlying PtdIns3P mode of action, specifically through PtdIns3P-binding effectors such as FYVE and PHOX proteins have been partially explored in plants with main focus on Arabidopsis thaliana. Additionally, they have been underexplored in other plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 92 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Expression data for protonemata specifically (Agudelo-Romero et al ., 2020; Xiao et al ., 2011) indicated that levels of most ATG genes are higher in caulonemata grown in optimal conditions (Fig. S8B).…”
Section: Resultsmentioning
confidence: 99%
“…Expression data for protonemata specifically (Agudelo-Romero et al ., 2020; Xiao et al ., 2011) indicated that levels of most ATG genes are higher in caulonemata grown in optimal conditions (Fig. S8B).…”
Section: Resultsmentioning
confidence: 99%
“…S2c). According to the phylogenetic analysis of FYVE domain‐containing proteins, FYVE4 seems to be a plant‐specific protein with putative homologues found only in plants, but not in yeast and animals (van Leeuwen et al ., 2004; Agudelo‐Romero et al ., 2020). A Blast search in 27 plant genomes representing all major evolutionary lineages of land plants (Phytozome 11; http://www.phytozome.jgi.doe.gov) indicated that putative homologues of Arabidopsis FYVE4 protein were present in all land plants, including the early‐divergent land plant Marchantia polymorpha (liverworts) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Arabidopsis contains 11 PX proteins ( van Leeuwen et al, 2004;Agudelo-Romero et al, 2020; Figure 4 ). These include six Sorting Nexin proteins (SNX1, SNX2a, SNX2b, and SNX3-5), two phospholipase Ds (PLDf1 and 2), and three EREX (Endosomal Rab Effector with PX domain; EREX, EREL1, and EREL2) proteins (see Supplemental Text T2).…”
Section: Px Domainsmentioning
confidence: 99%
“…The PI3P-binding pocket is formed by the conserved WxxD, (R/K)(R/K)HHCR, and RVC motifs at the end of the b1-strand, whereby the lipid's head group ends up parallel to the b1 strand. Due to its small size, PPI specificity is mostly indirect, with only PI3P or PI5P fitting inside the FYVE pocket, with PI3P being preferred (Kutateladze and Overduin, 2001;Agudelo-Romero et al, 2020). Membrane localization is further positively influenced by coincidence detection, either via homodimerization, additional lipid-binding motifs, or protein-protein interaction (Lystad and Simonsen, 2016).…”
Section: Fyve Domainsmentioning
confidence: 99%
See 1 more Smart Citation